1961
DOI: 10.1083/jcb.11.1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Localization of Acid Phosphatase in Rat Liver Cells as Revealed by Combined Cytochemical Staining and Electron Microscopy

Abstract: Discrete localization of stain in pericanalicular granules was found in 10 µ frozen sections of formol-phosphate-sucrose-fixed liver stained by the Gomori acid phosphatase technique and examined in the light microscope. The staining patterns, before and after treatment with Triton X-100 and lecithinase, were identical with those previously reported for formol-calcium-fixed material treated in the same way, and it can be assumed that the stained granules are identical with "lysosomes." Examination in the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
3

Year Published

1965
1965
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(73 citation statements)
references
References 25 publications
2
68
0
3
Order By: Relevance
“…For fine structural localization of acid phosphatase, tissues were fixed at 4°C for 18 hours in either 10 per cent formalin containing 2 per cent calcium acetate, or sucrose phosphate formalin (Holt and Hicks, 1961), or for 2 hours in the glutaraldehyde solution prior to processing according to methods described by Holt andHicks (1961) andMiller (1962). After fixation, tissues were rinsed 3 times for 5 minutes each in 7.5 per cent sucrose at 4°C, frozen quickly in this solution on a microtome hammer with dry ice, and sectioned at 40 tz in the cryostat.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…For fine structural localization of acid phosphatase, tissues were fixed at 4°C for 18 hours in either 10 per cent formalin containing 2 per cent calcium acetate, or sucrose phosphate formalin (Holt and Hicks, 1961), or for 2 hours in the glutaraldehyde solution prior to processing according to methods described by Holt andHicks (1961) andMiller (1962). After fixation, tissues were rinsed 3 times for 5 minutes each in 7.5 per cent sucrose at 4°C, frozen quickly in this solution on a microtome hammer with dry ice, and sectioned at 40 tz in the cryostat.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…Il a d'ailleurs été constaté depuis longtemps (Barka et Anderson, 1962 ;Holt et Hicks, 1961) que la réaction des phosphatases acides par la méthode de Gomori devait être interprêtée avec prudence étant donnée la fréquence des fausses réactions positives (précipités ou simple ombrage au plomb des structures cellulaires). Par contre une très faible quantité d'enzymes peut être présente dans le parasite sans être révélée par cette réaction relativement peu sensible aux faibles concentrations de phosphatase acide (Barka et Anderson, 1962 ;Holt et Hicks, 1961).…”
Section: Discussionunclassified
“…Par contre une très faible quantité d'enzymes peut être présente dans le parasite sans être révélée par cette réaction relativement peu sensible aux faibles concentrations de phosphatase acide (Barka et Anderson, 1962 ;Holt et Hicks, 1961).…”
Section: Discussionunclassified
“…In addition, we found ACPase in endosomelike vesicles, which are present in the cytoplasm around the bile canaliculus and just below the plasma membrane of the sinusoidal surface. A positive reaction for ACPase in the endosomelike vesicles has not been clearly shown by the enzyme cytochemistry (4,13,20). The present study showed that ACPase is associated with the plasma membrane and with the lysosomal membrane, as reported by Parenti and coworkers (19).…”
Section: Discussionmentioning
confidence: 99%
“…After the pioneering work of Sheldon and coworkers (24), the "lead capture" method of Gomori (10) was adapted to electron microscopy, and the ultrastructural localization of ACPase in various tissues and cells under normal and pathological conditions has been since described by many investigators (2,4,7,13,18). ACPase seems to be one of the most extensively studied enzymes that are cytochemically demonstrable.…”
mentioning
confidence: 99%